Survival in Advanced Epithelial Ovarian Cancer Associated with Cardiovascular Comorbidities and Type 2 Diabetes Mellitus. - Slavchev, Stanislav; Kornovski, Yavor; Yordanov, Angel; Ivanova, Yonka; Kostov, Stoyan; Slavcheva, Svetoslava (Current Oncology, 2021)
Background: Ovarian carcinoma (OC) is usually diagnosed at an advanced stage, necessitating a multimodal approach that includes surgery and systemic therapy. The incidence of OC is approximately five times higher in women over 65 years of age. Cardiovascular comorbidities and type 2 diabetes mellitus, both prevalent at this age, can influence therapeutic strategy and have an adverse effect on survival. Objectives: Our study aimed to determine the impact of cardiovascular diseases and diabetes mellitus on survival in advanced ovarian cancer. Materials and methods: From 2004 to 2012, we retrospectively studied 104 patients with advanced epithelial ovarian cancer (FIGO stage II–IV) who underwent surgical treatment at the Gynecology Clinic, St. Anna University Hospital, Varna, Bulgaria. Patients were followed for an average of 90 (52–129) months. We divided the study population into two groups: those with concurrent cardiovascular diseases and type 2 diabetes mellitus (CVD) and those without these comorbidities (No-CVD group). Overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS) were compared between groups using Kaplan–Meier survival analysis. Cardiovascular comorbidities and diabetes mellitus were evaluated for their prognostic value for survival using multivariate Cox proportional regression analysis adjusted for age, stage of OC, grade and histological type of the tumor, ascites presence, residual tumor size (RT), performance status, and type of hysterectomy. Results: The Kaplan–Meier analysis showed reduced OS and DSS in the CVD group compared to the No-CVD group. The median OS was 24.5 months (95% CI 18.38 months) and 38 months (95% CI 26, not reached), respectively (Log-rank p = 0.045). The median DSS was 25.5 months (95% CI 19.39 months) and 48 months (95% CI 28, not reached), respectively (Log-rank p = 0.033). The Cox regression multivariate analysis established a lower (by 68%) overall survival rate for the CVD patient group than the No-CVD group, approaching statistical significance (HR 1.68, 95% CI 0.99, 2.86, p = 0.055). Cardiovascular diseases and diabetes were associated with a 79% reduction in DSS (HR 1.79, 95% CI 1.02, 3.13, p = 0.041) and a twofold increase in the risk of disease progression (HR 2.05, 95% CI 1.25, 3.37, p = 0.005). Conclusions: According to our study, cardiovascular comorbidities and diabetes may adversely affect OC survival. Optimal control of cardiovascular diseases, diabetes mellitus, and their risk factors may be beneficial for patients with advanced OC. Further research involving a larger patient population is necessary to establish these comorbidities as independent prognostic factors.